Flexible Bioelectronics: Blending Electronics with the Human Body: A Pathway toward a Cybernetic Future (Adv. Sci. 10/2018). Issue 10 (17th October 2018) - Mehrali, Mehdi; Bagherifard, Sara; Akbari, Mohsen; Thakur, Ashish; Mirani, Bahram; Mehrali, Mohammad; Hasany, Masoud; Orive, Gorka; Das, Paramita; Emneus, Jenny; Andresen, Thomas L.; Dolatshahi‐Pirouz, Alireza
Abstract : The usage of prosthetics such as retina, brain‐machine and neural implants along with the projected importance of technical health aids indicates that we are entering a cybernetic era. In article number1700931, Alireza Dolatshahi‐Pirouz and co‐workers discuss the advances in this field with a special focus on how flexible electronics are being used by scientists to reshape this field into a readily implementable technology.